Studies on the behaviour of Anomala opacicollis (Pér) - Miles, Peter Wallace (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1954)
[Summary]: The larvae of Anomala opacicollis (Pér), of Melolonthid and of other Rutelid species, attack tobacco in Southern Rhodesia, and are more commonly called "whitegrubs". Whitegrubs are widespread in the sandveld areas where tobacco is grown and, at the Trelawney Station of the Tobacco Research Board of Southern Rhodesia, where this work was done, A. opacicollis was the predominant species. An account oÂ£ the one year life cycle is given. The adults eat the leaves of various indigenous trees and an account of an experiment on the food preferences of A. opacicollis adults is given, and the main food sources in the Trelawney area are listed. An experiment is described which shows that the beetles prefer to lay their eggs in the veld or in manured broken land rather than in normal ploughed lands. The larvae are erratically distributed in lands and experiments on larval movement suggest that this is mainly due to concentration of the larvae at discrete concentrations of organic matter in the soil. The temperature and moisture condition of the top 3" of soil are found to be those which attact the larvae. It is suggested that tho larvae prefer and move to soil which contains the lowest amount of moisture which keeps the soil air spaces saturated. lt appears that the preferred temperature decreases with increasing soil moisture content and it is suggested that this is due to the respiratory requirements of the larvae. Soil pH, compaction and fertiliser content and the presence of plants do not appear to influence larval movements. A theory is developed concerning the mechanism of movements in the soil and it is suggested that, in the absence of a continuous gradient, the speed but not the direction of movement is influenced by conditions to which the larvae are sensitive. Evidence in support of thie theory is given. Studies on the survival of larvae at different soil moisture contents and temperatures show that conditions in the top 3" of soil are not likely to be lethal in spite of the high temperatures and low moisture contents found there. The relation of whitegrub behaviour to agricultural problems is discussed. Other workers published evidence indicating that early ploughed lands were attractive to whitegrubs; this is shown not to be the case and the previous evidence is re-interpreted. Such lands tend to contain concentrations of whitegrubs round the borders. The reason for this is discussed and it is suggested that lands should be ploughed early to confine whitegrub infestations in this manner. Soils low in fertility through repeated cultivation are commonly believed to contain more whitegrubs than virgin soil. However, behaviour studies suggest that it is the activity and not the size of the population which is affected by soil fertility. The time at which tobacco is planted is known to determine the extent of subsequent whitegrub damage. The reason for this is to be found in the life cycle of whitegrubs and the results of an experiment on time of planting in relation to whitegrub damage are given. Some insecticides are shown to be more repellant than others to A. opacicollis larvae and the influence of this fact on the assessment of soil insecticide effectiveness in the field is discussed. Reference is made to a method developed by the writer for the determination of insecticide effectiveness under the conditions of erratic whitegrub distribution which normally occur.
Keywords: Anomala -- Behavior -- Zimbabwe; Anomala -- Control -- Zimbabwe; Anomala -- Larvae -- Zimbabwe; Scarabaeidae -- Zimbabwe; Beetles -- Control -- Zimbabwe; Tobacco -- Diseases and pests -- Zimbabwe; Tobacco industry -- Zimbabwe; Insecticides -- Zimbabwe